Reconstructing project management - Morris, Peter W. G. (Chicester : John Wiley & Sons, 2013)
The book is designed to offer a thoughtful commentary on project management as it has been practiced and taught over the last 60 or more years, and as it may be over the next 20 to 40, drawing on examples from several industry sectors. Its thesis is that 'it all depends on how you define the subject' - that much of our present thinking about p.m. as traditionally defined is boring, sometimes conceptually weak or even flawed, and/or of limited application, whereas in reality what it can offer is exciting, challenging and potentially enormously useful. The book explores this hypothesis.
Introduction -- Constructing project management. Introduction to Part 1 -- Project management before it was invented -- Systems project management -- The project management knowledge base -- Developing project management -- Enterprise-wide project management (EWPM) -- The development of project management: summary -- Deconstructing project management. Introduction to Part 2 -- Control -- Organisation -- Governance and strategy -- Managing the emerging project definition -- Procurement and the project's commercial management -- Adding value, controlling risk, delivering quality, safely and securely -- People -- Reconstructing project management. Level 3: the institutional context -- Introduction to Part 3 -- The character of our PM knowledge -- Managing context -- Ethos: building sponsor value -- 'only connect' -- the age of relevance -- Summa. Summary and conclusions -- Appendices. Appendix 1: Critical success factor studies -- Appendix 2: 'Characteristics of successful megaprojects or systems acquisitions' -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Project management; Business; Management; BUSINESS & ECONOMICS -- Project Management; TECHNOLOGY & ENGINEERING -- Project Management; Project management; Electronic books